Invariant constant multi-valued mapping for the heat conductivity problem - Tukhtasinov, M.; Mustapokulov, K.; Ibragimov, Gafurjan (Institute for Mathematical Research, Universiti Putra Malaysia, 2019)
We consider a heat conductivity equation with boundary control. The problems of strong and weak invariance of constant multi-valued mapping are analyzed for this equation. The control function is given on the boundary and the problem is studied under various constraints on control. We obtain sufficient conditions of strong and weak invariance for the given multi-valued mapping.